Lack of association between miR-218 rs11134527 A>G and Kawasaki disease susceptibility. Issue 3 (22nd May 2018) - Pi, Lei; Fu, Lanyan; Xu, Yufen; Che, Di; Deng, Qiulian; Huang, Xijing; Li, Meiai; Zhang, Li; Huang, Ping; Gu, Xiaoqiong
Abstract : Kawasaki disease (KD) is a type of disease that includes the development of a fever that lasts at least 5 days and involves the clinical manifestation of multicellular vasculitis. KD has become one of the most common pediatric cardiovascular diseases. Previous studies have reported that miR-218 rs11134527 A>G is associated with susceptibility to various cancer risks. However, there is a lack of evidence regarding the relationship between this polymorphism and KD risk. The present study explored the correlation between the miR-218 rs11134527 A>G polymorphism and the risk of KD. We recruited 532 patients with KD and 623 controls to genotype the miR-218 rs11134527 A>G polymorphism with a TaqMan allelic discrimination assay. Our results illustrated that the miR-218 rs11134527 A>G polymorphism was not associated with KD risk. In an analysis stratified by age, sex, and coronary artery lesions, we found only that the risk of KD was significantly decreased for children older than 5 years (GG vs. AA/AG: adjusted OR = 0.26, 95% CI = 0.07–0.94, P =0.041). The present study demonstrated that the miR-218 rs1113452 A>G polymorphism may have an age-related relationship with KD susceptibility that has not previously been revealed.